Bi System Superconducting Fibres by the Laser-heated Pedestal Growth Method in Stable Magnetic Field - 葛云龙; 焦育宁; 杨院生; 刘传胜; 刘清民; 胡壮麟 (Chinese Science Bulletin, 1994)
1 Introduction The technology of the laser-heated pedestal growth (LHPG) in making single crystalsand fibres is based on the Czochralski technique, which makes use of a laser as heaterto produce all kinds of high melting temperature oxide single crystal materials. Inthe early 1980s, the Bell Laboratory in USA produeed some kinds of single cryatalsand fibres having special properties by using this technique. Since 1986, high-T_csuperconducing fibres have been produced in many laboratories of LHPG insome countries, and the Institute of Metal Research, Academia Sinica,also built an experimental apparatus financially supported by the NationalSuperconducting Centre specially to study the superconducor.
Keywords: stable magnetic field; laser-heated pedestal growth; Bi system superconducting fibre.